Peningkatan Hasil Belajar Matematika Melalui PjBL, dan STEM, Berbantuan Webex untuk Siswa SMP - Pangestuti, Wahyu Cahyaning; Masbur, Masbur (SCAD Independent, 2025)
Based on the writer's experience, the material of congruence and similarity is material that is considered difficult by students and the learning outcomes of this material are unsatisfactory. Previously, learning in this material used Project Based Learning (PJBL), had not implemented Science Technology Engineering Mathematics (STEM) and had not used any applications. This study aims to improve the learning outcomes of class IXE students of SMP Negeri 4 Yogyakarta in the material of congruence and similarity in the 1st semester of the 2019/2020 school year. by applying the PPA and STEM learning model assisted by the Webex application. This type of research is a classroom action research (PTK) which consists of 2 cycles. The qualitative analysis model is the Miles & Hubberman model which includes: data reduction (sorting out important, relevant, and meaningful data from useless data), descriptive presentation (narrative, visual images, tables) with a systematic and logical flow of presentation, conclusion of research results shows: (1) the increase in the average pre-test and post-test cycle 1, 25.17 points and cycle 2, 15.82 points, exceeding the research success indicator, namely an increase of at least 5; (2) The increase in the average results of student activity is 8%, teachers are 4%, student questionnaires are 11.4%, all above the indicators of research success are at least 2%. Based on the description, the actions in this study can improve student learning outcomes.